KEBOCORAN 91 JUTA DATA PRIBADI KONSUMEN APLIKASI TOKOPEDIA: STUDI NORMATIF DAN TANGGUNGJAWAB - Christmas, Grace (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
Personal data leaks in Indonesia have been occurring continuously. On March 20, 2020, approximately 91 million user accounts and 7 million merchant accounts were allegedly leaked from Tokopedia, encompassing information such as user ID, email, full name, date of birth, gender, phone number, and hashed passwords. Research conducted regarding this data breach utilized normative research analysis methods, focusing on qualitative descriptive data. This approach allows researchers to understand and analyze the legal context governing personal data protection in Indonesia. In this case, the analysis focuses on several applicable laws aimed at protecting users' personal data from unwanted leaks and court rulings related to consumer personal data breaches from Tokopedia. Based on the ruling, Tokopedia was found to have committed a breach of contract, meaning the platform failed to meet its legal obligations and responsibilities to safeguard users' personal data. Consumers who feel harmed by this leak have the right to file a lawsuit or report the case to the Minister of Communication and Information of the Republic of Indonesia. This aims to hold Tokopedia accountable as an Electronic System Provider, aligning with established regulations and ensuring the protection of consumer rights in an increasingly complex digital era.